Pendampingan Budaya Literasi Dengan Metode ABCD (Asset Based Community Development) Terhadap Santri Kelas 3 SMP di Asrama Al Maliki Pondok Pesantren Sunan Drajat Banjarwati Banjaranyar Paciran Lamongan - Muhammad Haris; Nur Ahid; M. Ridhowan (PT FORMOSA CENDEKIA GLOBAL, 2022)
Since the emergence of pesantren, it has given color to Indonesia. In fact, there are many traditions and cultures of Islamic boarding schools that are still preserved untul the curret era, one of which is literacy culture; writing, reading, and listening. Literacy has also been taught at the time of the prophet Muhammad, so it is not uncommon for curricula such as sorogan dan bandongan to be raught by ustadz/ustazah to santriwan and santriwati. Traditional/cultures that are even feared to disappear in this era are still active in pesantren. Thesurrounding community, and alumni in their vision of forming the character and spirit of scholarship for the nation and state.